Kontribusi Manajemen Sarana Prasarana Terhadap Mutu Layanan Pembelajaran Di SMA Negeri 1 Ciampea - Rahmawati, Ima; Rifki Baharudin, Titan; Dafenta S, Hadi (JURNAL KAJIAN ISLAM MODERN, 2023)
The quality of learning services is synthesized as an activity to achieve customer expectations standards in improving academic and non-academic services that create value and provide benefits systematically and have good service to continue to improve quality and needs that create satisfaction in the utilization of all the potential inherent in the resources owned optimally and demands the organization to be better, more competitive in achieving organizational goals and able to compete against the times. This study aims to explain 1) the infrastructure available at SMA Negeri 1 Ciampea Bogor. 2) the quality of learning services available at SMA Negeri 1 Ciampea Bogor. 3) the contribution of infrastructure management to the quality of learning services at SMA Negeri 1 Ciampea Bogor. This study involved 40 teachers at SMA Negeri 1 Ciampea Bogor, the sample was obtained by non-probability sampling technique with a saturated sample. The research method used is a quantitative method with a correlational approach. The data collection technique used a closed questionnaire with a Likert scale and the data analysis technique used was simple linear regression. Based on the results of simple linear regression analysis, the management of infrastructure has a positive and significant effect on the quality of learning services. This shows that the stronger the contribution of infrastructure management, the higher the quality of learning services produced by teachers. Therefore, to foster the quality of learning services, teachers are expected to pay more attention to the management of infrastructure in these school institutions.